Determinants Of Internal Audit Quality at the Inspectorate General of The Ministry Of PUPR - Muhammad Fauzan Fachrezy; Syanni Yustiani (Polytechnic of State Finance STAN, 2025)
This research aims to determine the determinants of internal audit quality at the Inspectorate General of the Ministry of PUPR. The research is a causal study carried out using quantitative methods using PLS-SEM analysis. Data processing in this research uses the SmartPLS 4 application. The results of this research are that the integrity and professional behavior of auditors is proven to have a positive and significant influence on the quality of the internal audits they produce, while the factors of independence, objectivity, competence and organizational support are proven to have no significant influence on quality. internal audit. Apart from that, it was also proven that organizational support cannot moderate the relationship between integrity, independence, objectivity, competence and professional behavior of auditors on the quality of internal audits of the Inspectorate General of the Ministry of PUPR. Therefore, to improve the quality of internal audits at the Inspectorate General of the Ministry of PUPR, training can be carried out that can improve the integrity and professional behavior of auditors.